Patient-appraised beneficial moments during inpatient psychiatric treatment - Cosima Locher; Ramin Mansour; Helen Koechlin; Stefan Büchi (BMC, 2020)
Abstract Background Psychiatric inpatients receive a multidisciplinary treatment approach, covering psychiatry, nursing, occupational therapy, and psychology. Research findings reveal that the effectiveness of any treatment is associated with three types of factors: specific (e.g., treatment techniques), common (e.g., clinician-patient relationship, patients' expectations) and extra-therapeutic. However, there is little published research on the factors and events which inpatients themselves consider to be beneficial ('beneficial moments'). Methods Inpatients (N = 107) of a psychiatric clinic completed a questionnaire to elicit their appraisal of beneficial moments. A qualitative content analysis was applied. The coding procedure was conducted independently by two authors. Results Self-appraised beneficial moments were found in five areas: therapy-specific components (number of quotations, N = 204), positive relationships (N = 140), clinical setting and environment (N = 52), inpatients' new insights (N = 36), and factors unrelated to either therapy or the clinic (N = 30). In total, 44% of the quotations were related to specific factors, 49% to common factors, and 7% to extra-therapeutic factors. Conclusions Inpatients judge both specific and common factors as crucial for the therapeutic benefit they gain during their stay at the clinic. Our results differ from meta-analytical findings, where the impact of specific factors on symptom improvement has shown to be much smaller (i.e., 17%) than appraised by patients in our study (i.e., 44%). Our study underlines the importance of a patient-centred care approach as well as shared decision making and patient-clinician communication. For clinical practice, knowledge of inpatients' perspectives on beneficial moments is crucial in order to reinforce precisely these therapeutic components.